The Right of States to Remain within International Law and Its Impact on the Conditions of Jihad Al-Talab (Defensive Jihad) According to Ancient and Contemporary Jurisprudential Schools: A Comparative Study - Alkilani, Abdallah I Zaid; Almazrouai , Hamad (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This research aims to explore jihad al-talab (defensive jihad), its ruling, manifestations, and contemporary application within the context of the state's right to exist. Methods: The research employs three approaches: inductive, descriptive, and comparative. It analyzes religious texts on defensive jihad and international laws concerning the right to exist. The study clarifies meanings, explains purposes, and explores means to achieve defensive jihad's objectives, considering contemporary jurisprudence. Results: Defensive jihad serves to promote the call to Allah and deter enemies. It is obligatory and involves well-equipped regular armies for homeland defense with deterrent power. Muslim states should also utilize soft power to uphold Islamic law's sovereignty and serve the call to Allah. In the contemporary era, it is achieved through positive international relations, agreements ensuring freedom of religious expression, and maintaining sufficient strength for deterrence. Conclusions: The maqasid (objectives) approach confirms that defensive jihad does not infringe upon states' right to exist. Its ruling should be understood in light of protecting freedom of religion and respecting agreements. War is not the sole means to achieve state policies; soft tools like preaching, education, and cultural institutions should be activated according to Islamic law's objectives. International agreements regulating freedom of worship and conscience can be utilized.